Efeito da densidade de plantas de Bracharia decumbens Stapf sobre o crescimento inicial de mudas de Eucalyptus grandis W. Hill ex Maiden - De Toledo, Roberto Estêvão Bragion; Dinardo, Weber; Bezutte, Alexandre José [UNESP]; Da Costa Aguiar Alves, Pedro Luís [UNESP]; Pitelli, Robinson Antonio [UNESP] (My University, 2001)
In order to verify the effect of Brachiaria decumbens plant density on the initial growth of Eucalyptus grandis plants, one assay was conducted under semi-controlled conditions of soil fertility and humidity. Dark red Latossol, collected from the arable layer, was used as substrate in 50 liters amianthus cement boxes. One seedling of Eucalyptus was planted in each box. Fifteen days later, seedlings of B. decumbens were transplanted on the same box. The treatments consisted of 0, 4, 8, 12, 16, 20, 24, 28, 32, 36, 40, 60, 80, 100, and 120 plants of B. decumbens. The experimental design was the complete randomized design, with 15 treatments and four replicates. The Eucalyptus plants that lived with B. decumbens were evaluated for stem diameter, plant high, leaf area, and dry weight of stem, branches and leaves. B. decumbens plants were evaluated for dry weight of aerial parts. B. decumbens, at the density level of four plants per m 2 and over, reduced of the initial growth of the Eucalyptus plants. B. decumbens reduced on average 27.78% stem diameter, 18.47% plant high, 70.56% leaf number, 63.26% leaf area, and 55.22%, 77.29% and 55.30% of stem, branch and leaf dry weight, respectively. Plant high was not a good parameter to evaluate the B. decumbens interference.
Effect of Brachiaria decumbens Stapf density on the initial growth of Eucalyptus grandis W. Hill ex Maiden plants
Keywords: Brachiaria grass; Density; Eucalyptus; Interference